Adverse childhood experiences (ACEs) research: A bibliometric analysis of publication trends over the first 20 years. (February 2021) - Struck, Shannon; Stewart-Tufescu, Ashley; Asmundson, Aleiia J.N.; Asmundson, Gordon G.J.; Afifi, Tracie O.
Abstract: Background: The relative health and robustness of a field of research can be approximated by assessing peer reviewed journal publication trends for articles pertinent to the field. To date, there have been no such assessments of the burgeoning research on adverse childhood experiences (ACEs). Objective: The overall goal of this study was to examine ACEs research trends using bibliometric methods. More specifically, we sought to describe observed publication trends of the ACEs literature from its inception in the late 1990s. We also analyzed the nature of ACEs publications with regard to key characteristics of main outcomes, levels of analysis, and populations of primary focus. Methods: A search was conducted using Scopus to identify English language papers on ACEs published in peer-reviewed journals between 1998 and 2018. The primary field of research was determined by having independent raters code the title of the publishing journal into distinct categories. Main research outcomes were similarly coded. Results: A total of 789 articles on ACEs appearing in 351 different academic journals were published between 1998 and 2018. There was considerable growth in the number of ACEs papers published over the past several years. General medicine and multidisciplinary research were the most frequent of 12 primary fields of research characterizing ACEs research. Of 16 primary outcomes on which ACEs research focused, the most common were mental health and physical health. Conclusion: Significant growth in ACEs research over the past several years suggest the field is thriving. Observed publication trends and publication characteristics are discussed briefly.